PLANT GROWTH STIMULATION OF LIGNITE HUMIC ACIDS. PART-]]]: EFFECT OF AMMONIUM HUMATE ON SEED COTTON YIELD AND FIBER QUALITY - Khan, A Rasheed; Mir, Surraiya (Biological Sciences - PJSIR, 2002)
Effects of variou s concentrations of humic acids (as ammonium humate) ranging from 0 .05 to 1.0 kg ha·1 on the cuWvation of cotton at the slit loam soil without using any chemical fertilizer were accomplished . Results showed significant effects of humic acids on seed cotton yield, boll weight, seed/boll, bolls/plant and lint (%). Maximum yield of cotton was recorded at a dose of 1.0 kg ha·1 humic acids. The soil of Karachi already contains enough amount of phosphorou s fortilizer for cotton cultivation. Encouraging effects of humic acids on fiber quality related parameters were also noted.